Evaluation of a Focused Cardiac Ultrasound Protocol in a Pediatric Emergency Department. Issue 4 (April 2021) - Riera, Antonio; Weeks, Bevin; Emerson, Beth L.; Chen, Lei
Abstract : Objectives: The objective of this study was to evaluate the implementation of a focused cardiac ultrasound (FoCUS) protocol in a pediatric emergency department (PED). Methods: We conducted a cross-sectional, observational, quality improvement project in a PED of an urban tertiary care children's hospital. A FoCUS protocol was collaboratively developed by pediatric cardiology and pediatric emergency medicine. This included a reference document with definitions, indications, image acquisition guidelines, and interpretation expectations. We measured physician-sonographer performance against pediatric cardiologist interpretation of stored cine clips as our reference standard. Focused cardiac ultrasound interpretation was dichotomized for the presence or absence of pericardial effusion, depressed left ventricular function, and chamber size abnormalities. Run charts were used to compare the number FoCUS performed each month and the quality of captured cine clips with those from the previous year. Results: Ninety-two FoCUSs were performed by 34 different physician-sonographers from January to December 2016. The prevalence of FoCUS abnormalities was 18.5%. For pericardial effusion, sensitivity was 100% (95% confidence interval [CI], 48%–100%) and specificity was 99% (95% CI, 94%–100%). For depressed function, sensitivity was 100% (95% CI, 54%–100%) and specificity was 99% (95% CI, 94%–100%). For chamber size abnormalities, sensitivity was 100% (95% CI, 54%–100%) and specificity was 95% (95% CI, 89%–99%). The median number of monthly FoCUS increased from 1 (preprotocol) to 5 (postprotocol), and the median rate of adequate studies increased from 0% to 55%. Conclusions: We report the collaborative development and successful implementation of a PED FoCUS protocol. Physician-sonographer interpretation of FoCUS yielded acceptable results. Improvements in FoCUS utilization and cine clip adequacy were observed.